Comparative study on plasma mineral profiles of normal cyclic and pregnant cows with infertile cows of North-Western Himalayan region of India - KUMAR, PRAVESH; SINGH, MADHUMEET; SHARMA, AKSHAY; KUMAR, RAVINDRA; SOOD, PANKAJ (The Indian Journal of Animal Sciences, 2023)
The present study was undertaken to study the effect of different minerals on infertility in cows (n=885) belonging to different Northern Western Himalayan regions of the state. Cows suffering from different types of infertility such as endometritis, anestrus, silent estrus and cows showing metestrual bleeding were evaluated and compared with normal cyclic and pregnant cows. Minerals evaluated were calcium, phosphorous, magnesium, copper, zinc, sodium, and potassium. The levels of calcium were statistically low in anestrus and silent estrus cows when compared with normal cyclic and pregnant animals. The levels of phosphorus were significantly low in cows suffering from endometritis and in cows showing abnormal metestrual bleeding in comparison to normal cyclic cows. Similarly, magnesium levels were high in pregnant cows than other categories. Copper was statistically high in normal cyclic and pregnant cows. Similarly, sodium and potassium were statistically high in normal cyclic cows than infertile and repeat breeder cows.